A General Gaussian Interest Rate Model Consistent with the Current Term Structure. (5th September 2012) - Di Francesco, Marco
Abstract : We describe an extension of Gaussian interest rate models studied in literature. In our model, the instantaneous spot rate r is the sum of several correlated stochastic processes plus a deterministic function. We assume that each of these processes has a Gaussian distribution with time-dependent volatility. The deterministic function is given by an exact fitting to observed term structure. We test the model through various numeric experiments about the goodness of fit to European swaptions prices quoted in the market. We also show some critical issues on calibration of the model to the market data after the credit crisis of 2007.